MEDICAL COMMUNICATORS FOR FAMILY MEDICINE - Romanov, V. O.; Pyatchanina, T. V.; Kovyrova, O. V. (Medical Informatics and Engineering, 2020)
Background. Assessing the adequate level of health of patients and the effectiveness of treatment methods requires modern clinical studies of «quality of life» through the use of various standardized questionnaires, both general purpose and designed for individual nosologies. The assessment of quality of life, which is performed by the patient using questionnaires, together with the traditional medical opinion of the doctor, gives a complete and objective description of the patient's condition. The goal is to develop software to automate quality of life assessment based on the standardized MOS SF-36 questionnaire for a mobile tablet computer using the results as information support for making objective medical decisions. Materials and methods. The method of estimating the quality of life according to the MOS SF-36 questionnaire is based on the instruction for calculating the indicators of quality of life, for which an applied computer program has been developed. This applied computer program calculates quality of life indicators on 8 scales. To estimate by a family doctor or general doctor the quality of life with supporting the proposed medical communicator there were used Java programming language and integrated environment Android Studio 3.6.3, which provides storage of survey data and calculated indicators of quality of life on recommended scales. An appropriate database has been created. Results. The prototype was a medical information communicator based on a mobile tablet computer (V. M. Glushkov Institute of Cybernetics of NASU and Shupyk National Medical Academy of Postgraduate Education), the software of which contains five subsystems with a set of reference and information functions to support the activities of the doctor and interactive communication with the patient, in particular, in case of limitation of his communication capabilities as a result of the disease or trauma. Conclusions. The analysis of the subject area of common standardized questionnaires to assess the quality of life of patients revealed the optimal for automation — The Medical Outcomes Study Short Form (MOS SF-36) — a short form of non-specific questionnaire for quality of life, for which there is a Ukrainian-adapted version. The initial stage of development of software for automation of quality of life assessment based on the standardized questionnaire MOS SF-36 for mobile tablet computer, the results of which can serve as information support for making informed medical decisions, has been completed.інформаційні комунікатори